The Sustainability Inclusion in Project Contracts and its Impact on the Performance of UAE Public Sector Projects - ALAJAMI, SAEED (2024)
Sustainable project management practices considering the triple bottom line remain vital for the efficient execution of the project activities and the overall success and performance of projects. This requires careful and controlled planning and monitoring of the project activities, controlling the execution to ensure compliance with sustainable practices throughout by including relevant clauses in the contracts for efficient project delivery across the overall project management life cycle. The research aims to investigate the impact of the influence of sustainability in project contracts and its impact on the performance of UAE public sector projects. The research has been developed with the consideration of positivism philosophy, deductive approach and explanatory design. The research has integrated primary data collection sources thereby collecting information from online surveys. The analysis of the data has been conducted with the inclusion of descriptive analysis and inferential analysis. However, concerning inferential analysis, tests of regression and correlation have been integrated to facilitate hypothesis testing. The survey included feedback from 100 respondents who have been from public sector projects in the UAE. The descriptive analysis reflected that sustainability inclusion has been essential for public sector projects as it improved the performance and quality of the same. The project managers have been found to integrate three kinds of sustainability such as economic, social and environmental. The inferential analysis further reflected that there has been a direct relationship between the performance of the projects and sustainability inclusion. The government policy makers need to establish guidelines based on sustainability legislation to improve the environmental performance of the public sector construction projects in the UAE. Worker training is an effective strategy for improving sustainability practices with the use of contracts. Government agencies require proactiveness in spreading awareness about the significance of sustainability and using it for determining the viability of the tenders and awarding the projects to the contractors. Keywords: sustainability, contract, construction, public sector projects, UAE, triple bottom line etc.